ヒグマをめぐる札幌市民の意識と行動 - 亀田, 正人; KAMEDA, Masato; カメダ, マサト (室蘭工業大学, 2014)
application/pdf The goal of this study is to provide basic information on the attitudes and behaviors of residents in Sapporo toward brown bears (Ursus arctos) and bear management and, by doing so, to contribute to more informed management and policy decisions. The author conducted a mail survey among the residents of Sapporo living near the points where bears or their signs were reported in 2010 or 2011. The result showed: (1) the level of acceptance of bears is as high as half in the sample, (2) mass media and neighborhood associations play important roles in dispersing information and knowledge about bears, (3) respondents want the municipal government to conduct a variety of activities, including bear habitat investigation and public education, and (4) farmers and orchard owners also want more direct measures to avoid product losses. 学術論文 departmental bulletin paper